#INDONESIAGELAP DI PLATFORM X: Perwakilan Perlawanan Masyarakat Madani Melalui Aktivisme Hashtag - Gladys Intan Juniarta; Anabelle Graciani Nathaniel Sirait; Muradi (Journal Publicuho, 2025)
#IndonesiaGelap on Platform X, which emerged on February 17, 2025, with over 81,900 posts, is interpreted as a representation of civil society resistance and digital activism in contemporary Indonesia. This qualitative study uses literature review methods to explore how social media has become a primary public space for voicing aspirations and criticism of government policies, particularly approval of the revision of the Indonesian National Armed Forces Law and other issues, such as education budget cuts. The word "Gelap" symbolises the closure of public access and concerns over the decline of democracy and civil supremacy, reflecting the collective memory of the New Order era. This hashtag serves as an instrument for mobilising public opinion, strengthening solidarity, and providing symbolic accountability to the state. While this movement expands democratic space and reduces barriers to participation, the findings also highlight limitations, including the risk of slacktivism (clicktivism) and repression through regulations such as the ITE Law, demonstrating the paradox of digital democracy where online participation must translate into sustained, organised action offline to achieve structural change.